1999
DOI: 10.1177/107769909907600209
|View full text |Cite
|
Sign up to set email alerts
|

Auto Trade Policy and the Press: Auto Elite as a Source of the Media Agenda

Abstract: This study, based on content analysis, showed that the auto elite set the agenda for the New York Times and the Detroit News, both of which were inclined to have their news coverage of the auto trade conflicts between the United States and Japan biased toward fair trade, not free trade. Additionally, the News was more likely than the Times to be more biased, especially when the conflicts were mounting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Elite theory (Dye, 2013; Key, 1967; Mills, 1956) in general and framing (Entman, 1993), indexing (Bennett, 1990; Groshek, 2008), and political contest (Wolfsfeld, 2004) concepts in particular all highlight that resourceful political and business elites can have a strong or even decisive say in public policy decision-makings. Associated theoretical cum empirical evidence also shows that the highest executive leaders are the ultimate decision-makers, and business elites are tremendous power-wielders, particularly when they maneuver to collaborate with politicians to rally society around their preferred flag (Chang, 1999). But when politicians are accused of collusions or corruptions and there is a backlash over domestic public policies, it is highly probable that the existing consensus becomes split between the government and the interest group (Banting & Myles, 2016; Entman, 2003; Kingdon, 2011).…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elite theory (Dye, 2013; Key, 1967; Mills, 1956) in general and framing (Entman, 1993), indexing (Bennett, 1990; Groshek, 2008), and political contest (Wolfsfeld, 2004) concepts in particular all highlight that resourceful political and business elites can have a strong or even decisive say in public policy decision-makings. Associated theoretical cum empirical evidence also shows that the highest executive leaders are the ultimate decision-makers, and business elites are tremendous power-wielders, particularly when they maneuver to collaborate with politicians to rally society around their preferred flag (Chang, 1999). But when politicians are accused of collusions or corruptions and there is a backlash over domestic public policies, it is highly probable that the existing consensus becomes split between the government and the interest group (Banting & Myles, 2016; Entman, 2003; Kingdon, 2011).…”
Section: Discussion Conclusion and Limitationsmentioning
confidence: 99%
“…In the United States context, a thin elite circle encompasses prestige managers and journalists in the news business, particularly those closely allied with the White House and Congress (Mills, 1956). As predominant news sources, political and business elites can help build news agendas and issue frames by effectively using their political or financial resources (Chang, 1999; K. K. Kim, 2003; Koduah, Agyepong, & van Dijk, 2016).…”
Section: Framing and Frame Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources within the oil industry may also impact news media coverage and congressional discussion. For example, Chang 54 studied auto elites' influence on the news media agenda on trade in the automotive industry. Similar research can examine the influence of oil industry corporations on the news media agenda.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Kim (2000) revealed how differently the New York Times and the Washington Post utilized their news sources: they repeatedly cited Chinese student demonstrators, who characterized the Tiananmen movement in terms of a struggle for democracy, free speech and a free press; while they relied more on Korean government sources to characterize the Kwangju movement as a 'rebellion' or a 'student-led disturbance ' (2000: 30). In his study of the press coverage of the auto trade dispute between the USA and Japan, Chang (1999) found that the press heavily depended on auto elite and government officials for the information; therefore, it was biased toward fair trade themes rather than toward free trade themes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%